Quality and safety in long-term care in Ontario: The impact of language discordance - Batista, Ricardo; Prud'homme, Denis; Rhodes, Emily; Hsu, Amy; Talarico, Robert; Reaume, Michael; Guérin, Eva; Bouchard, Louise; Desaulniers, Jacinthe; Manuel, Douglas; Tanuseputro, Peter (Journal of the American Medical Directors Association, 2021)
Objectives This study compared quality indicators across linguistic groups and sought to determine whether disparities are influenced by resident-facility language discordance in long-term care. Design Population-based retrospective cohort study using linked databases. Setting and Participants Retrospective cohort of newly admitted residents of long-term care facilities in Ontario, Canada, between 2010 and 2016 (N=47,727). Individual residents' information was obtained from the Resident Assessment Instrument Minimum Data Set (RAI-MDS) to determine resident's primary language, clinical characteristics, and health care indicators. Measures Main covariates of interest were primary language of the resident and predominant language of the long-term care facility, which was determined using the French designation status as defined in the French Language Services Act. Primary outcomes were a set of quality and safety indicators related to long-term care: worsening of depression, falls, moderate-severe pain, use of antipsychotic medication, and physical restraints. Multivariable logistic regression models were used to assess the impact of resident's primary language, facility language, and resident-facility language discordance on each quality indicator. Results Overall, there were few differences between francophones and anglophones for quality and safety indicators. Francophones were more likely to report pain (10.9% vs 9.9%; P = .001) and be physically restrained (7.3% vs 5.2%; P < .001), whereas a greater proportion of anglophones experienced worsening of depressive symptoms (24.0% vs 22.9%; P = .001). However, quality indicators were generally worse for francophones in Non-Designated facilities, except for pain, which was more commonly reported by francophones in French-Designated facilities. Anglophones were more likely to be physically restrained in French-Designated facilities (6.7% vs 5.1%; P < .001). Conclusions and Implications For francophones, quality indicators tended to be worse in the presence of resident-facility language discordance. However, these findings did not persist after adjusting for individual- and facility-level characteristics, suggesting that the disparities observed at the population level cannot be attributed to linguistic factors alone.

Pratique # 21 : ConnectAînés / Francsavoir (pancanadienne) - Benoît, Josée; Michel, Jean Nephetaly (2021)

Pratique # 22 : Bien vieillir chez soi / Soutien à domicile (pancanadienne) - Benoît, Josée; Michel, Jean Nephetaly (2021)

Co-development of a Web-based hub (eSocial-hub) to combat social isolation and loneliness in Francophone and Anglophone seniors in linguistic minority context (Quebec, Manitoba, and New Brunswick): Protocol for a mixed methods interventional study - Beogo, Irissa; Ramdé, Jean; Nguemeleu Tchouaket, Eric; Sia, Drissa; Bationo, Nenila Jean-Claude; Collin, Stéphanie; Anne, Abdoulaye; Gagnon, Marie-Pierre (JMIR Research Protocols, 2021)
Background: The first wave of the COVID-19 pandemic has severely hit Canadian nursing facilities (81% of deaths). To this toll, public health measures (eg, visitation restriction) have subsequently deepened the social isolation and loneliness of residents in nursing facilities (NFs), especially those in linguistic minority settings: Anglophone institutions in Quebec and Francophone institutions outside Quebec. However, very few COVID-19 initiatives targeting these populations specifically have been documented. Given the limited number of NFs serving linguistic minorities in Canadian populations, families and loved ones often live far from these facilities, sometimes even in other provinces. This context places the digital solutions as particularly relevant for the present COVID-19 pandemic as well as in the post–COVID-19 era. Objective: This project aims to co-develop a virtual community of practice through a web-based platform (eSocial-hub) to combat social isolation and loneliness among the older people in linguistic minority settings in Canada. Methods: An interventional study using a sequential mixed methods design will be conducted. Four purposely selected NFs will be included, 2 among facilities in Manitoba and 2 in New Brunswick; and 2 Anglophone NFs in Quebec will serve as knowledge users. The development of eSocial-hub will include an experimental 4-month phase involving the following end users: (1) older people (n=3 per NF), (2) families of the participating older people (n=3 per NF), and (3) frontline staff (nurse and health care aid; n=2 per NF). Results: Activities and solutions aiming at reducing social isolation and loneliness will be implemented and then evaluated with the project stakeholders, and the best practices generated. The assessment will be conducted using indicators derived from the 5 domains of the Consolidated Framework for Implementation Research. The project will be led by an interdisciplinary team and will involve a multisectoral partnership. Conclusions: The project will develop a promising and generalizable solution that uses virtual technology to help reduce social isolation and loneliness among the older people.

Naviguer le maintien à domicile en communautés de langue officielle en situation minoritaire rurales : enjeux et pistes de solutions - Dupuis-Blanchard, Suzanne; Caissie, Julie (Reflets, 2021)
Le vieillissement de la population dans les provinces de l’Atlantique est une réalité courante en plus d’une composition géographique rurale et la présence de communautés de langue officielle en situation minoritaire (CLOSM). Les objectifs de cette étude descriptive qualitative étaient de 1) comprendre les services utilisés pour le maintien à domicile, et 2) déterminer les services nécessitant une amélioration pour l’accès en français. Vingt-six (n=26) personnes âgées ont participé à cette étude en région rurale de l’île du Prince Édouard. Les résultats témoignent des difficultés d’accès aux services pour le maintien à domicile tout en offrant des pistes de solutions pour l’améliorer. Mots-clés : Maintien à domicile, vieillissement, communautés de langue officielle en situation minoritaire, communauté rurale, services, recherche qualitative

Practice # 3: The Pavillon Omer Deslauriers: A Francophone Unit at Bendale Acres (Ontario) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2021)
fs-ref-orig: Savard, J., Savard, S., van Kemenade, S., Benoît, J., Buhay, C., Youbi, S., & Kubina, L.A. (2021, updated 2025). Practice # 3: The Pavillon Omer Deslauriers: A Francophone Unit at Bendale Acres (Ontario). In: GReFoPS. Directory of Innovative Practices in Health and Social Services in Official Language Minority Contexts. https://www.grefops.ca/directory_innovative_practices.html fs-code-orig: Savard-2025b

Pratique # 10 : Les points de service satellites (Ontario) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2021)
fs-ref-orig: Savard, J., Savard, S., van Kemenade, S., Benoît, J., Buhay, C., Youbi, S., et Kubina, L.A. (2021). Pratique # 10 : Les points de service satellites (Ontario). Dans : GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire. https://www.grefops.ca/ repertoire_pratiques_novatrices.html fs-code-orig: Savard-2021d

Pratique # 11 : The Information and Support Guide for Caregivers (Québec) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2021)
fs-ref-orig: Savard, J., Savard, S., van Kemenade, S., Benoît, J., Buhay, C., Youbi, S., et Kubina, L.A. (2021). Pratique # 11 : The Information and Support Guide for Caregivers (Québec). Dans : GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire. https:// www.grefops.ca/repertoire_pratiques_novatrices.html fs-code-orig: Savard-2021e

Pratique # 12 : Les Lunchs-causeries au Centre de services communautaires Vanier (Ontario) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2021)
fs-ref-orig: Savard, J., Savard, S., van Kemenade, S., Benoît, J., Buhay, C., Youbi, S., et Kubina, L.A. (2021, mise à jour 2025). Pratique # 12 : Les Lunchs-causeries au Centre de services communautaires Vanier (Ontario). Dans : GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire. https://www.grefops.ca/repertoire_pratiques_novatrices.html fs-code-orig: Savard-2025g

Pratique # 13 : Une infirmière de Santé publique dans un centre de services communautaires qui assure l’aiguillage des aînés (Ontario) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2021)
fs-ref-orig: Savard, J., Savard, S., van Kemenade, S., Benoît, J., Buhay, C., Youbi, S., et Kubina, L.A. (2021, mise à jour 2025). Pratique # 13 : Une infirmière de Santé publique dans un centre de services communautaires qui assure l’aiguillage des aînés (Ontario). Dans : GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire. https://www.grefops.ca/repertoire_ pratiques_novatrices.html fs-code-orig: Savard-2025h

Le vieillissement francophone en contexte minoritaire. Défis et opportunités - Siméon, Frantz; Couturier, Yves (Reflets, 2021)